Advances to High‐Performance Black‐Phase FAPbI3 Perovskite for Efficient and Stable Photovoltaics. Issue 5 (17th February 2021) - Chen, Haoran; Chen, Yuetian; Zhang, Taiyang; Liu, Xiaomin; Wang, Xingtao; Zhao, Yixin
Abstract : Formamidinium lead iodide (FAPbI3 )‐based perovskites have become one of the most promising candidate materials for high efficiency and thermally stable perovskite solar cells due to their outstanding optoelectrical properties and high thermal stability. However, the phase degradation of black FAPbI3 perovskite phase to yellow nonperovskite phase at ambient conditions restricts the long‐term stability of FAPbI3 perovskite solar cells. Such phase transition can be affected by various conditions especially under humidity and thermal stress. To address the phase instability issue, tremendous research efforts have been devoted to crystallizing high‐quality black phase and refraining the photoinactive δ‐phase formation. Herein, first, these research efforts are summarized for the deposition of FAPbI3 perovskite film and the stabilization of pure α‐FAPbI3 perovskite, then the FAPbI3 structural features and phase transformation behavior are discussed. The corresponding strategies for maintaining black phase and enhancing optical properties of FAPbI3 perovskite is also concluded. Second, the latest progress and achievement of stabilizing black‐phase FAPbI3 are discussed through various methods including additives, doping, and alloying, interfacial engineering, etc. Finally, the future research directions and strategies to achieve high efficiency and stable FAPbI3 ‐based perovskite solar cells are described. Abstract : Herein, the phase behavior of FAPbI3 crystal structure is discussed and the advanced strategies are summarized to maintain stable black‐phase FAPbI3 perovskite films through various process including additives, doping, and alloying, interfacial engineering, etc. Finally, the future study directions are described to achieve high efficiency and stable FAPbI3 ‐based perovskite solar cells.